Street-based Corruption In The Philippines: Exploring Kotong Frame Alignments Between Enforcers And Motorists In A City In Metro Manila - Bodegon, Hannah Frances C.; Villanueva, Prince Aian G.; Esber, Janessa Polly J.; Fernando, Jon Christian A.; Andrew, John; Guevarra, C. Guevarra; Valeriano, Charles Daniell B. (Penerbit Universiti Sains Malaysia (USM Press), 2017)
Corruption is a pervasive problem in the Philippines. Previous studies have focused on institutions and culture as factors behind the persistence of corruption in the country. Moreover, the emphasis has been on corruption that occurs within the bureaucracy. In this qualitative, exploratory study, we explored the possibility of the shared understanding, the frame alignments between the local state authorities and drivers as a possible explanation behind the persistence of street-based form of corruption known as kotongan or kotong.